Perlindungan Penggunaan Logo Stasiun TV oleh Konten Kreator Tiktok di Kota Medan Perspektif Fatwa MUI - Marlyn, Hazlya; Zulham, Zulham (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The development of entertainment application technology is very rapid making people follow the trend of content creators to voice their ideas, has both positive and negative impacts. The positive change is that people can express ideas about traveling, cooking, and even creating their own comedy. The parody carried out by one of the Tiktok platforms has violated IPR by using the Indosiar TV station logo as parody material whose content is not in accordance with the purpose of the series being parodied. The purpose of this article is to describe MUI Fatwa No. 1/MUNAS/5/2005 regarding the use of the Indosiar TV logo by Medan Tiktokers. This research is normative legal research. The results of this research show violations committed by Medan Tiktokers regarding the use of the Indosiar TV logo in their content in terms of MUI Fatwa No. 1/MUNAS/5/2005 constitutes a violation of design rights, patent rights, trademark rights and copyright. If we look at the content, it is stated that Tiktokers have committed acts by using, distributing, plagiarizing, and reproducing the Indosiar TV logo for commercial purposes and it is declared haram. This research recommends that Indosiar TV take legal action against individuals who parody their series using the TV logo